Adiabatic Temperature Rise Test of Cemented Sand and Gravel (CSG) and Its Application to Temperature Stress Prediction of CSG Dam. (6th July 2020) - Jiang, Minmin; Cai, Xin; Guo, Xingwen; Liu, Qinghui; Zhang, Tianye
Abstract : An adiabatic temperature rise test of cemented sand and gravel (CSG) is conducted, a model for temperature rising of CSG is proposed, and its application to temperature stress prediction of CSG dam is presented. Adiabatic temperature rise tests are first conducted to investigate the temperature rise properties of CSG material with different cementing agent contents. The results demonstrate that the hydration reaction time is longer for CSG material with higher cementing agent content, and a linear relationship is presented between cementing agent contents and final value of adiabatic temperature rise. Then, a calculation model considering different cementing agent contents is developed based on the regression analysis of the test data. The proposed model is implanted into the ANSYS software platform for predictions of temperature distributions and stress fields of a typical CSG dam. The results show that the distributions of temperature and temperature stress are similar to those of roller compacted concrete (RCC) dam. Due to the high temperature stress at the long intermittent surface and downstream surface of the dam, the thermal insulation measures on the surface of the dam should be considered in the CSG dam with high cementing agent contents and in the severe cold environment. Therefore, it cannot be generally considered that the temperature control of the CSG dam does not need to be considered, and it should be determined according to the specific working conditions.